Referred scapula pain from C6 or C7 cervical spinal stenosis - Marena Willeford; Sierra Willeford (Open Journal of Pain Medicine - Peertechz Publications, 2019)
Objective: The aim of the present study was to determine if there exists referred medial scapula pain from C6 or C7 cervical spinal stenosis. Scapula pain of neurologic origin at present is felt to be mediated mainly by C5 through the dorsal scapular nerve. An interventional spine clinic noted a series of patients with medial scapula pain without C5 stenosis, however many of these patients had either C6 or C7 stenosis. Methods: The charts of 278 patients seen in an interventional spine clinic over an 11 year period from 2008 to 2018 who were diagnosed with cervical radiculopathy based on location of pain were reviewed. 135 of these had cervical MRI imaging. Data was collected to evaluate for a correlation of the level of cervical stenosis with the location of pain at the medial border of the scapula.